(3QSGdI aj GdcjejGAs - (3CMeO Hf Ydj Hf jhSa, CHh GdYHGS GdHhfj,J (B622 (3g` s
(3ChdgG (B:s
(3bGd GYde jG CNj Cf GdUfYI GdEdgjI heYQaJgG eeG jJYPQ Gdhbha Ydi cGaI EMGWJgG s
(3BNQgG (B:s
(3Hd Jchf ajg QWhHI cGTeY ai GdUja aMjfFP Edb efg OQgekG Ydi QWd ef GdbeQ jbhe TeSkG HEPf Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdYGTQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B174 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B25s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs